Biomass production from Kluyveromyces spp. by using cheese whey - Mahmood, Karzan T. (Sulaimani Journal for Pure and Applied Sciences, 2015)
Cheese whey was used as a medium for producing yeast biomass from Kluyveromyces lactis DSM 70800 and Kluyveromyces fragilis. The best conditions for yeast biomass production were 35oC with agitation speed of 150 and 200 rpm for Kluyveromyces fragilis and Kluyveromyces lactis DSM 70800 respectively. Both strains can grow in a wide range of pH. The maximum biomass yield recorded when whey with pH 6.5 was used. The crud protein based on dry weight was relatively high and the crud protein % of Kluyveromyces lactis DSM 70800 (50.56%) was insignificantly higher than that was obtained for Kluyveromyces fragilis (49.53%) while the protein yield was insignificantly higher for Kluyveromyces fragilis. On the other hand, the essential and non-essential amino acids were present in a various amount, among these amino acids arginine was present in high level in both strains which has the good nutritive value especially for children.
Keywords: Biomass; Yeast; Kluyveromyces; Cheese whey